Journal of Economic Literature - American Economic Association (Pittsburgh, PA American Economic Association, 1996)
The Journal of Economic Literature (JEL), first published in 1969, is designed to help economists keep abreast of the vast flow of literature. JEL issues contain commissioned, peer-reviewed survey and review articles, book reviews, an annotated bibliography of new books classified by subject matter, and an annual index of dissertations in North American universities
Journal of Economic Literature (JEL) is published quarterly in March, June, September and December Vol. 7 (1996) - vol. 21 (1983) were donated to MAS by BZU , Vol. 22 (1984)- Vol. 32 (1994) are not available at the library
Keywords: Economics; ECONOMICS; LITERATURE; DATA BASES; PERIODICALS